Indonesian Phonological Interference with Japanese by Japanese Language Learners Undiksha - Pramana Pradnyana, Ida Bagus Made; Patmi, Ni Putu Dita Candra; Mahendra, Ida Bagus; Hermawan, Gede Satya (Journal of Language Education Studies and Applied Linguistics, 2025)
The result of this research shows that there is phonological interference between Indonesian and Japanese by students of the Japanese Language Education Study Program, Undiksha. This research aims to identify the influence of the mother tongue, Indonesian on Japanese by using spoken Japanese text (phonology). Phonological interference was found to occur in nasal pronunciation, long vowels or “chouon”, pronunciation of post-alveolar consonants, additional phonemes, pronunciation of double consonants “sokuon”, and pronunciation of liquids. These results were obtained using Weinreich’s theory, which discusses language interference. The method used is the listening method with recording and note-taking techniques through the pronunciation of the text being read. The data analysis method used in this research is the matching method with the sorting technique.